A Historical View of Active Assisted Living - Colantonio, Sara; Aleksic, Slavisa; Agius, Jean Calleja; Camilleri, Kenneth; Cartolovni, Anto; Climent-Pérez, Pau; Lambrinos, Lambros; Cristina, Stefania; Despotovic, Vladimir; Ekenel, Hazım Kemal; Erakin, Mustafa Ekrem; Florez-Revuelta, Francisco; et al. (My University, 2025)
Active assisted living (AAL) aims to use innovative technologies to create supportive, inclusive, and empowering applications and environments that enable older, impaired or frail people to live independently and stay active longer in society. This chapter provides an introduction to the main concepts of AAL, provides a brief history of the evolution of such technologies, and gives a functional view of how AAL system architecture can be conceptualized. It then provides a taxonomy of AAL technologies and applications, followed by technological underpinnings of audio- and video- based AAL.
Keywords: ADAS; Ageing; Gerontology; Philosophy of Artificial Intelligence; Virtual and Augmented Reality; Wearable Technology; Ambient Assisted Living Technologies for Aging Populations